A Case for Cross-Border Governance? A Comparative Trend Assessment of COVID-19 Transmission, Vaccination, and Outcomes Among 35 Nations in Europe Across 18 months. (2nd May 2023) - Cuschieri, Sarah; Cuschieri, Andrea; Farrugia, Elysia; Diacono, Emily; Balzan, Elaine; Grupetta, Miguel; Vella, Alessia; Cutajar, Catriona; Formosa, Martina; Barbara, Matthias; Mintoff, Franziska; Shaw, Conor; et al.
Abstract: Objective: Coronavirus disease 2019 (COVID-19) spread globally, including across Europe, resulting in different morbidity and mortality outcomes. The aim of this study was to explore the progression of the COVID-19 pandemic over 18 mo in relation to the effect of COVID-19 vaccination at a population level across 35 nations in Europe, while evaluating the data for cross-border epidemiological trends to identify any pertinent lessons that can be implemented in the future. Methods: Epidemiological data were obtained from European Centre for Disease Prevention and Control and Our World in Data databases while Ministry of Health websites of each respective country and local newspapers were used for COVID-19-related vaccination strategies. Case, mortality, and vaccination incidence comparative analyses were made across neighboring countries. Results: Similar morbidity and mortality outcomes were evident across neighboring countries over 18 mo, with a bidirectional relationship evident between cumulative fully vaccinated population and case fatality rates. Conclusion: Countries' COVID-19 outcome is related on national mitigative measures, vaccination rollouts, and neighboring countries' actions and COVID-19 situations. Mass population vaccination appeared to be effective in reducing COVID-19 case severity and mortality rates. Vaccination equity and pan-European commitment for cross-border governance appear to be the way forward to ensure populations' return to "normality."